Evaluation of Acceptance Of E-Learning Information System Using Tam (Technology Acceptance Model) At Esa Unggul University - Fauzia Achmad, Yunita; Fernando Raista, Rizky; Yulhendri; Parlindungan (International Journal of Psychosocial Rehabilitation, 2020)
Improving the quality of education is an important thing that must be done by every educational institution. The use of information technology tools that are currently widely used in universities is E-Learning. Lack of socialization about e-learning information systems from universities, the difficulty of students capturing material given by lecturers when courses are conducted online (E-Learning), lack of interaction between students and lecturers in e-learning information systems. This study aims to analyze the benefits and convenience factors for the acceptance of E-learning information systems using the Technology Acceptance Model (TAM). The sampling technique uses saturated samples, with 45 respondents. For data analysis techniques using multiple linear regression techniques with quantitative research types, and data processing tools using SPSS 16.0 software for windows. The results of this study are the perceived usefulness variable has a t-count value (1715) <t-table (1,680) and H1 is accepted, the perceived ease of use variable has a t-count value (1,158) <t-table (1,680) and H2 is accepted, and the results of the f-test have the value of f-count (1682)> f-table (3.21) or the value of sig (0.000) <α (0.10) and H3 is accepted it can be concluded reliable.